Design, synthesis, and optimization of a novel ternary photocatalyst for degradation of cephalexin antibiotic in aqueous solutions - Zeynab Abdeyazdan; Mohammad Rahmati; Arjomand Mehrabani-Zeinabad; Masoud Habibi Zare (Scientific Reports)
Abstract The widespread use of antibiotics in veterinary and medical applications has increased the possibility of water contamination, which causes adverse effects such as increased bacterial resistance in humans and other organisms. This study, investigates the efficient removal of cephalexin (CPX) using Fe doped TiO2–Bi2O3 nanocomposite, synthesized via the simple sol–gel method as a visible active photocatalyst. The weight fraction of Fe (3–7 wt%), and Bi2O3 (7–11 wt%) was optimized. The Fe–TiO2–Bi2O3 nanocomposite with a weight fraction of 3 and 11% for Fe and Bi2O3 has the best photocatalytic activity for Cephalexin degradation. The characteristics of photocatalyst with optimum composite (3 wt% of Fe and 11 wt% Bi2O3) were also investigated by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), diffuse reflectance spectra (DRS) and FTIR. The DRS spectra approved that the adsorption wavelength of Fe-doped TiO2–Bi2O3 is in the visible light range. The influence of amount of catalyst (0.5–1.5 g/L), Cephalexin concentration (5–15 mg/L) and initial pH of the solution (3–9) in on CPX photodegradation was modeled and optimized using central composite design based on response surface methodology. Maximum cephalexin degradation Under visible light irradiation (50 W LED, 395–400 nm) was achieved about 74% at 5 mg/L of CPX, 1.5 g/L catalyst loading and pH of 9 in 240 min. Moreover, using a 15W UV lamp under the same conditions increased the degradation efficiency to 96% at 120 min. Considering the high potential of Fe–TiO2/Bi2O3 nanocomposite in removing Cephalexin antibiotics, it can be considered a suitable candidate for removing antibiotics from contaminated water sources.